2005
DOI: 10.1128/jvi.79.4.2528-2540.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Narrow Pores at the Fivefold Symmetry Axes of Adeno-Associated Virus Type 2 Capsids Reveals a Dual Role in Genome Packaging and Activation of Phospholipase A2 Activity

Abstract: Adeno-associated virus type 2 (AAV2) capsids show 12 pores at the fivefold axes of symmetry. We mutated amino acids which constitute these pores to investigate possible functions of these structures within the AAV2 life cycle. Mutants with alterations in conserved residues were impaired mainly in genome packaging or infectivity, whereas few mutants were affected in capsid assembly. The packaging phenotype was characterized by increased capsid-per-genome ratios. Analysis of capsid-associated DNA versus encapsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
190
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(201 citation statements)
references
References 89 publications
(103 reference statements)
9
190
2
Order By: Relevance
“…There are also reports that mutation of AAV2 residues in the 5-fold channel, structurally adjacent to the HI loop, both in the ␤-ribbons that extend outward (with VR-II at its apex) and the residues on the interior narrow region of the channel, results in an inability of the capsid to package its genome (105,106). It has been suggested that this is principally due to altered Rep-VP complexes that form at the 5-fold channel, proposed to be the portal for DNA packaging.…”
Section: Fig 2 Aav Capsid Surfaces (A Cmentioning
confidence: 99%
“…There are also reports that mutation of AAV2 residues in the 5-fold channel, structurally adjacent to the HI loop, both in the ␤-ribbons that extend outward (with VR-II at its apex) and the residues on the interior narrow region of the channel, results in an inability of the capsid to package its genome (105,106). It has been suggested that this is principally due to altered Rep-VP complexes that form at the 5-fold channel, proposed to be the portal for DNA packaging.…”
Section: Fig 2 Aav Capsid Surfaces (A Cmentioning
confidence: 99%
“…Capsid assembly probably occurs in the nucleolus and is then relocalized into the nucleoplasm, with some influence of Rep proteins. The colocalization of the empty assembled capsid, the Rep proteins and the ssDNA AAV genome in the nucleoplasm allows the encapsidation process to occur (Im and Muzyczka, 1989;Wistuba et al, 1997;King et al, 2001;Bleker et al, 2005). Finally, the novel viral particles exit the cell, probably by an unknown exocytosis mechanism.…”
Section: Viral Systemsmentioning
confidence: 99%
“…These three capsid proteins differ among them at the N terminus. VP1, VP2 and VP3 assemble in a molar ratio of 1:1:10, respectively, forming a near-spherical protein shell of 60 subunits that leads to perfect icosahedral symmetry (Bleker et al, 2005). A conserved phospholipase A 2 (PLA2) motif, located within the VP1 N-terminal region (Zádori et al, 2001), was reported to have a biological significance in AAV2 infection (Girod et al, 2002).…”
Section: Viral Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant AAV vectors were quantified by replicative Dot Blot titration 50 giving infectious titers expressed as replicating units (r.u.). Instead of HeLa cells, HeLaRC cells expressing Rep and Cap proteins 35 were used.…”
Section: Construction Of Viral Vectorsmentioning
confidence: 99%